2022
DOI: 10.1111/bcp.15241
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative administration of ketorolac compared to other drugs for pain control after third molar surgery: A meta‐analysis of double‐blind, randomized, clinical trials

Abstract: The aim of this study was to evaluate the analgesic effectiveness and adverse reactions of ketorolac in comparison with other drugs when administered postoperatively after third molar surgery.Methods: PubMed and Google Scholar were utilized to search for articles comparing the efficacy and safety of ketorolac and other analgesic agents after third molar surgery. Data from papers with a lower risk of bias were recorded. The overall evaluation of analgesia onset, general and subgroup evaluation of the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…However, Tirupathi et al conducted a review study and concluded that further clinical trials were needed to prove the effectiveness of ketorolac in pain control ( 24 ). By contrast, Isiordia et al showed that the administration of 30 mg ketorolac, compared to 1 - 10 mg parecoxib, after the surgical removal of third molars resulted in better analgesic effects and higher patient satisfaction ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Tirupathi et al conducted a review study and concluded that further clinical trials were needed to prove the effectiveness of ketorolac in pain control ( 24 ). By contrast, Isiordia et al showed that the administration of 30 mg ketorolac, compared to 1 - 10 mg parecoxib, after the surgical removal of third molars resulted in better analgesic effects and higher patient satisfaction ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane Collaboration’s risk of bias tool was used to determine the risk of bias in all studies that met the inclusion criteria [ 1 , 2 , 3 , 4 , 37 , 38 , 39 ]. Two independent investigators assessed the risk of bias.…”
Section: Methodsmentioning
confidence: 99%
“…Two independent investigators assessed the risk of bias. The differences between their evaluations were discussed until a consensus was reached [ 1 , 2 , 3 , 4 , 37 , 38 , 39 ]. The clinical reports with a high risk of bias were excluded (at least one red ball).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations